2015
DOI: 10.1016/j.fjps.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the analgesic activity and safety of ketorolac in whole body fractionated gamma irradiated animals

Abstract: Please cite this article as: Aly S, Mahmoud MF, Hassan SHM, Fahmy A, Evaluation of the analgesic activity and safety of ketorolac in whole body fractionated gamma irradiated animals, Future Journal of Pharmaceutical sciences (2015), Abstract:This study was performed to evaluate the analgesic activity and the toxicity of ketorolac in normal and fractionated (1.5 Gy/day/4 days) γ-irradiated animals. Determination of brain serotonin content and serum prostaglandin level were also undertaken. The analgesic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Results obtained in the present study revealed mild alterations in the kidney function, reflected as a significant increase in urea of KT/WR-treated rats and a significant decrease in the creatinine level of both WR and KT/WR-treated groups. These altered parameters were in accordance with several reports reflecting a disturbed kidney function (Aly et al, 2015;Hörl, 2010;Kim & Joo, 2007;Pelligand et al, 2015) More recently, Lucas et al (2018) reported that NSAIDs increase the risk of developing nephrotoxicity and acute tubular necrosis and they recommended that this condition be well evaluated. The authors concluded that NSAIDs, selective and non-selective, directly interfere with renal function due to prostaglandin inhibition, and suggested acute sodium retention, which is the main cause of the overfilling effect due to arterial hypertension and edema (Chana et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Results obtained in the present study revealed mild alterations in the kidney function, reflected as a significant increase in urea of KT/WR-treated rats and a significant decrease in the creatinine level of both WR and KT/WR-treated groups. These altered parameters were in accordance with several reports reflecting a disturbed kidney function (Aly et al, 2015;Hörl, 2010;Kim & Joo, 2007;Pelligand et al, 2015) More recently, Lucas et al (2018) reported that NSAIDs increase the risk of developing nephrotoxicity and acute tubular necrosis and they recommended that this condition be well evaluated. The authors concluded that NSAIDs, selective and non-selective, directly interfere with renal function due to prostaglandin inhibition, and suggested acute sodium retention, which is the main cause of the overfilling effect due to arterial hypertension and edema (Chana et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Ketorolac is considered a potent analgesic with moderate anti-inflammatory effects (Schwier & Tran, 2016), although it has certain harmful effects on vital body organs such as the liver, kidney, and gastrointestinal tract (Aly et al, 2015;Bally et al, 2017;Tomic et al, 2008). During the recent years, an increasing number of studies have been published concerning the nephrotoxic effects of NSAIDs and anticoagulants (Chana et al, 2014;Lanas & Chan, 2017;Ozcan et al, 2012;Sriuttha, Sirichanchuen, & Permsuwan, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no liver damage, and impaired metabolism and function may be attributed to the ketorolac treatment in the chicks which is in accordance with another study in the animals (Aly 2015).…”
supporting
confidence: 91%
“…Ketorolac is a non‐steroidal anti‐inflammatory drug developed by Syntex . With clinical preparation form of tromethamine, Ketorolac possesses the pharmacological activity of being antipyretic, analgesic and anti‐inflammatory . Its analgesic effect is similar to aspirin, but antipyretic properties 20 times that of aspirin .…”
Section: Introductionmentioning
confidence: 99%